2023
DOI: 10.1002/pd.6357
|View full text |Cite
|
Sign up to set email alerts
|

Position statement from the International Society for Prenatal Diagnosis on the use of non‐invasive prenatal testing for the detection of fetal chromosomal conditions in singleton pregnancies

Abstract: Key points What is already known about this topic? In 2015, the International Society for Prenatal Diagnosis (ISPD) published its first position statement on the use of non‐invasive prenatal testing (NIPT) to screen for aneuploidy. Widespread uptake across the globe and subsequent published research has shed new light on test performance and implementation issues. What does this study add? This new position statement replaces the 2015 statement with updated information on the current technologies, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 127 publications
(223 reference statements)
0
17
0
Order By: Relevance
“…36 The second publication, is the position statement from the ISPD on implementation models and they concluded that NIPT for the common autosomal aneuploidies performs sufficiently well to be offered in primary or contingent screening models. 37 Therefore, ISPD did not endorse primary screening by NIPT as the only option.…”
Section: The Argument Againstmentioning
confidence: 99%
“…36 The second publication, is the position statement from the ISPD on implementation models and they concluded that NIPT for the common autosomal aneuploidies performs sufficiently well to be offered in primary or contingent screening models. 37 Therefore, ISPD did not endorse primary screening by NIPT as the only option.…”
Section: The Argument Againstmentioning
confidence: 99%
“…However, NIPT was just over the horizon and in 2013 Prenatal Diagnosis devoted two consecutive issues to this revolutionary technology and published a position statement from the International Society for Prenatal Diagnosis Aneuploidy Screening Committee. In this issue we are pleased to present the new ISPD Position Statement on NIPT for the detection of fetal chromosome conditions in singleton pregnancies, addressing the many clinical and research questions that have emerged since the first statement 3 . As an international organization, ISPD recognizes that there are important population‐specific considerations in the organization of prenatal screening and diagnosis, and that a “one size fits all” approach to screening is not appropriate for our global membership.…”
Section: Figurementioning
confidence: 99%
“…In this issue we are pleased to present the new ISPD Position Statement on NIPT for the detection of fetal chromosome conditions in singleton pregnancies, addressing the many clinical and research questions that have emerged since the first statement. 3 As an international organization, ISPD recognizes that there are important population-specific considerations in the organization of prenatal screening and diagnosis, and that a "one size fits all" approach to screening is not appropriate for our global membership. We hope this updated guideline helps inform local health policy and clinical practice wherever the reader may be.…”
mentioning
confidence: 99%
“…NIPT is offered to all pregnant women as part of a nationwide screening program in the Netherlands. 1 It is a reliable method to screen for fetal trisomy 13, 18 and 21, but may also reveal other chromosome abnormalities in the placenta, the fetus and/or the mother. 2,3 Following an aberrant NIPT result, diagnostic testing in chorionic villi (CV) or amniotic fluid (AF) is required to verify whether the chromosome anomaly is present in the fetus as well.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Following an aberrant NIPT result, diagnostic testing in chorionic villi (CV) or amniotic fluid (AF) is required to verify whether the chromosome anomaly is present in the fetus as well. 1,4,5 If amniocentesis is performed, our standard procedure is to perform single nucleotide polymorphism (SNP) array on uncultured AF cells and, depending on the chromosomal aberration, also on the blood of the mother. If both results were normal or if mosaicism in AF was found, this was complemented with karyotyping or fluorescent in situ hybridization (FISH) investigations of cultured AF cell colonies (in situ method).…”
Section: Introductionmentioning
confidence: 99%